Lactose Bioelectricity on A Microbial Fuel Cell System Parallel Circuit using Lactobacillus bulgaricus - Adi Putra; Rahmad Nuryanto; Linda Suyati (JURNAL SAINS DAN MATEMATIKA, 2014)
Electrical energy needs in Indonesia is estimated to continue growing by 4.6% per year, and if there is nothing to be done to increase the production of electric energy, this figure will increase threefold by 2030. Microbial Fuel Cells (MFC) is one way to produce alternative electric energy by utilizing organic material as a substrate for bacterial metabolic activity that generate electricity. The aim of this study is to examine lactose bioelectricity in a parallel circuit MFC system using Lactobacillus bulgaricus to generate electrical energy. The principle of this study is bioelectrochemistry which is the chemical energy change into electrical energy involving redox reactions by utilizing microbes. This study used a dual chamber MFC system with salt bridge as a connector and conductor of protons from the cathode compartment to the anode compartment. An anode compartment contained the bacteria Lactobacillus bulgaricus and lactose substrate, while the cathode compartment contained electrolyte solution KMnO4 0.2 M and phosphate buffer solution with pH = 7. This study used a single circuit, parallel circuit 1 with 2 cells, and a parallel circuit 2 with 3 cells which were oriented to enlarge the produced electricity current. Bioelectricity of lactose produced power in a single series, parallel 1 and parallel 2 respectively were 72.58 x10-6 mWatt; 155.77 x10-6 mWatt; 270.28 x10-6 mWatt where the power generated was proportional to the parallel circuit electric current. Hence by the same potential difference, the power magnitude in parallel circuit 1 approached twice to the single circuit and the power magnitude in parallel circuit 2 approached three times to the single circuit